TOURISM STORYTELLING, DAMPAKNYA TERHADAP NIAT PERILAKU WISATA DI KAWASAN DANAU TOBA KABUPATEN SAMOSIR, SUMATERA UTARA - Pasaribu, Asmara Wildani; Ginting, Juni Anggraini; Andriani, Nukeu Novia (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
The Ministry of Tourism and Creative Economy affirmed the establishment of storynomics strategy based on cultural wealth and is part of tourist areas promotion carried out with storytelling narratives, packaged in interesting content based on local culture. This research took place in Huta Siallagan Samosir Lake Toba Cultural Tourism Area. It aims to see whether tourism storytelling has a positive impact on consumer tourism behaviour intentions through WOM Intention and re-visit or not. The survey was conducted online by spreading questioner to tourist and managers of tourist areas. The analysis method is frequency, reliability, factor, and regression. The hypothesis test results showed that education, description, uniqueness, emotions, uniqueness of property, and ease of understanding in tourism storytelling that influenced WOM Intention. Among all the influencing factors, ease of understanding in storytelling is dominant and followed by attractive property tourism storytelling also affects the Re-visit intention